Closing maize yield gaps in sub-Saharan Africa will boost soil N2O emissions - Leitner, Sonja; Pelster, David E.; Werner, Christian R.; Merbold, Lutz; Baggs, Elizabeth M.; Mapanda, Farai; Butterbach-Bahl, Klaus (Elsevier, 2020)
In sub-Saharan Africa (SSA), the most important staple crop is maize; the production of which is dominated by smallholder farming systems using low external inputs (<10 kg N ha−1) resulting in low crop yields and large yield gaps (difference between actual and potential yields). To assess increases in soil N2O emissions when closing maize yield gaps by increased fertilizer use, we reviewed the literature, developed a relationship between yield gaps and soil N2O emissions, and used it to scale across SSA. According to our analysis, N2O emissions from maize production will increase from currently 255 to 1755 ± 226 Gg N2O-N year−1 (+589%) if existing maize yield gaps are closed by 75%, increasing total anthropogenic N2O emissions for SSA by c. 50%.